Association between aspirin dose and subarachnoid hemorrhage from saccular aneurysms: A case-control study. (18th September 2018) - Can, Anil; Rudy, Robert F.; Castro, Victor M.; Yu, Sheng; Dligach, Dmitriy; Finan, Sean; Gainer, Vivian; Shadick, Nancy A.; Savova, Guergana; Murphy, Shawn; Cai, Tianxi; Weiss, Scott T.; et al.
Abstract : Objective: To determine the association between ruptured saccular aneurysms and aspirin use/aspirin dose. Methods: Four thousand seven hundred one patients who were diagnosed at the Massachusetts General Hospital and Brigham and Women's Hospital between 1990 and 2016 with 6, 411 unruptured and ruptured saccular intracranial aneurysms were evaluated. Univariable and multivariable logistic regression analyses were performed to determine the association between aneurysmal subarachnoid hemorrhage and aspirin use, including aspirin dose. Inverse probability weighting using propensity scores was used to adjust for potential differences in baseline characteristics between cases and controls. Additional analyses were performed to examine the association of aspirin use and rerupture before treatment. Results: In multivariate analysis with propensity score weighting, aspirin use (odds ratio [OR] 0.60, 95% confidence interval [CI] 0.45–0.80) was significantly associated with decreased risk of ruptured intracranial aneurysms. There was a significant inverse dose-response relationship between aspirin dose and aneurysmal subarachnoid hemorrhage (OR 0.65, 95% CI 0.53–0.81). In contrast, there was a significant association between aspirin use and increased risk of rerupture before treatment (OR 8.15, 95% CI 2.22–30.0). Conclusions: In this large case-control study, aspirin therapy at diagnosis was associated with a significantly decreased risk of subarachnoid hemorrhage, with an inverse dose-response relationship among aspirin users. However, once rupture has occurred, aspirin is associated with an increased risk of rerupture before treatment.